The terminator - Hurd, Gale Anne; Cameron, James ([Los Angeles, Calif. : Hemdale Home Video, 1984)
The'Terminator' (part man, part machine) is sent to present day Earth from the future on a deadly mission. His task is to kill a young woman whose life will have great significance in the decades to come. This mechanical monster from the future leaves behind him an unspeakable path of destruction which nothing can stop
Title from title screen
Special features: Terminator - retrospective (featuring James Cameron and Arnold Scwarzenegger) ; other voicer new special effect documentary ; terminated series ; stills gallery
Director, James Cameron ; producer, Gale Anne Hurd ; executive producers, John Daly, Derek Gibson ; writers, James Cameron, Gale Anne Hurd
Cast: Arnold Schwarzenegger, Michael Biehn, Linda Hamilton, Lance Henriksen, Paul Winfield
DVD Format
In English with optional English, Mandarin, Cantonese, Korean, Thai or Bahasa subtitles
Keywords: Science fiction films; Cyborgs -- Drama; Artificial intelligence -- Drama